Quantitative Determination of Steroidal Saponins of Semen Allii Fistulosi Using HPLC-ELSD and HPLC-MS - Zhancai Zheng; Deduo Xu; Wenquan Lu; Wansheng Chen; Yingbo Yang; Zhijun Wu (Journal of Analytical Methods in Chemistry)
In this study, high-performance liquid chromatography-evaporative light scattering detection (HPLC-ELSD) and HPLC-mass spectrometry (HPLC-MS) were employed for the quantitative analysis of steroidal saponins of Semen Allii Fistulosi. The HPLC-ELSD method was simple, accurate, and repeatable, and the recoveries were 97.91%∼99.77%. Similarly, the HPLC-MS method was rapid, sensitive, accurate, and reproducible, and the recoveries ranging from 95.61% to 99.70% in the control samples. The sensitivity of the HPLC-MS method was several times higher than that of the HPLC-ELSD method. These results collectively demonstrated that these methods are suitable for the content determination of steroidal saponins of Semen Allii Fistulosi and the identification of its plant source.